Identification of CRF34_01B, a second circulating recombinant form unrelated to and more complex than CRF15_01B, among injecting drug users in northern Thailand - Sodsai Tovanabutra (2018)
In Thailand, the circulating HIV-1 strains include CRF01_AE, subtype B, and their recombinants. Genotyping and full-genome sequencing had previously identified circulating recombinant form CRF15_01B within a cohort of 347 HIV-1-infected individuals enrolled in the Opiate Users Research (OUR) study in northern Thailand. Using an improved MHAbce in six to eight genome regions and archived OUR serum samples, seven strains were identified with a new and complex 01/B recombinant pattern in common, different from that of CRF15_01B. Complete sequencing of three strains, amplified from serum as overlapping half-genomes, confirmed their common recombinant structure, mostly CRF01_AE, but with segments of subtype B in pol and gp41, plus a region of frequent 01/B crossovers in pol. OUR strains 1969P, 2275P, and 2478P were from individuals without direct epidemiological linkage and thus establish CRF34_01B. More comprehensive HIV-1 prevention and treatment programs in IDU can help to limit the growing complexity of HIV-1 strains in Thailand. © Mary Ann Liebert, Inc.